Prevalence of URAT1 allelic variants in the Roma population. (1st December 2016) - Stiburkova, Blanka; Gabrikova, Dana; Čepek, Pavel; Šimek, Pavel; Kristian, Pavol; Cordoba-Lanus, Elizabeth; Claverie-Martin, Felix
ABSTRACT: The Roma represents a transnational ethnic group, with a current European population of 8–10 million. The evolutionary process that had the greatest impact on the gene pool of the Roma population is called the founder effect. Renal hypouricemia (RHUC) is a rare heterogenous inherited disorder characterized by impaired renal urate reabsorption. The affected individuals are predisposed to recurrent episodes of exercise-induced nonmyoglobinuric acute kidney injury and nephrolithiasis. To date, more than 150 patients with a loss-of-function mutation for the SLC22A12 ( URAT1 ) gene have been found, most of whom are Asians. However, RHUC 1 patients have been described in a variety of ethnic groups (e.g., Arab Israelis, Iraqi Jews, Caucasians, and Roma) and in geographically noncontiguous countries. This study confirms our previous findings regarding the high frequency of SLC22A12 variants observed. Frequencies of the c.1245_1253del and c.1400C>T variants were found to be 1.92% and 5.56%, respectively, in a subgroup of the Roma population from five regions in three countries: Slovakia, Czech Republic, and Spain. Our findings suggested that the common dysfunction allelic variants of URAT1 exist in the general Roma population and thus renal hypouricemia should be kept in differential diagnostic algorithm on Roma patients with defect in renal tubular urate transport. This leads to confirm that the genetic drift in the Roma have increased the prevalence of hereditary disorders caused by very rare variants in major population.